2019
DOI: 10.1111/1750-3841.14791
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the Antioxidant Activity, Water Solubility, and Dispersion Stability of Prickly Pear Cactus Fruit Extracts Using Argon Cold Plasma Treatment

Abstract: Microwave‐powered cold plasma (CP) treatment was evaluated as a means to increase the antioxidant activity, water solubility, and dispersion stability of prickly pear cactus fruit (Opuntia ficus‐indica (L.) Mill.) extract. The extract (2 g) was treated at various CP generation powers and treatment times at 25 °C to 28 °C. The antioxidant activity of the prickly pear cactus fruit extract increased by 1.8% and 1.7% after CP treatment at 750 W for 40 min and 856 W for 36 min, respectively. Both the water solubili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 43 publications
2
6
0
Order By: Relevance
“…Increasing the treatment time at the low level of generation power causes the antioxidant activity to increase gradually, but as the treatment time increases at the high level of generation power, the antioxidant activity increases rapidly. The results agreed with a previous study (Kim, Lee, & Min, 2019), in which they treated prickly pear extract using argon CP conducted by a low‐pressure microwave‐powered system and reported that increasing the treatment time initially caused the antioxidant activity to decrease, but at long duration, an increase in the antioxidant activity was found.…”
Section: Resultssupporting
confidence: 92%
“…Increasing the treatment time at the low level of generation power causes the antioxidant activity to increase gradually, but as the treatment time increases at the high level of generation power, the antioxidant activity increases rapidly. The results agreed with a previous study (Kim, Lee, & Min, 2019), in which they treated prickly pear extract using argon CP conducted by a low‐pressure microwave‐powered system and reported that increasing the treatment time initially caused the antioxidant activity to decrease, but at long duration, an increase in the antioxidant activity was found.…”
Section: Resultssupporting
confidence: 92%
“…Similar results were obtained by Sarangapani et al (2017) [32] in plasma-treated parboiled rice. The solubility of treated samples enhanced by 18 and 28% in T1 and T2 in contrast with C. These changes were identified due to the damage of complex structures to soluble components like amylose and amylopectin by the action of plasma reactive species (Kim et al 2019;Sarangapani et al 2016) [31] . Particle size of the flour impacts the dispersibility of the sample.…”
Section: Effect Of Given Treatments On Techno-functional Propertiesmentioning
confidence: 98%
“…Neither PPU treatment at all treatment conditions nor independent APPJ and IPL treatments altered the ABTS or DPPH radical scavenging activity of rice germ (p > 0.05; Tables 1 and 2). Previous studies have reported changes in the antioxidant activity of foods upon APPJ treatment, IPL treatment, and UV-C treatment (Aguiló-Aguayo et al 2017;Kim et al 2019). The reactive species generated by plasma can increase the antioxidant activity of food by dissociating agglomerates of antioxidants; in addition, it can also decrease the activity by the degradation of antioxidants in foods (Garofulić et al 2015;Kim et al 2019;Kovačević et al 2016).…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…Previous studies have reported changes in the antioxidant activity of foods upon APPJ treatment, IPL treatment, and UV-C treatment (Aguiló-Aguayo et al 2017;Kim et al 2019). The reactive species generated by plasma can increase the antioxidant activity of food by dissociating agglomerates of antioxidants; in addition, it can also decrease the activity by the degradation of antioxidants in foods (Garofulić et al 2015;Kim et al 2019;Kovačević et al 2016). IPL and UV can induce a photo-protective antioxidant defense response to increase antioxidant activity (Aguiló-Aguayo et al 2017;Denoya et al 2020;Pataro et al 2015).…”
Section: Antioxidant Activitymentioning
confidence: 99%